PENGARUH KOMPENSASI TERHADAP KINERJA MENGAJAR GURU - N Eli Rosilawati (Jurnal Tata Kelola Pendidikan, 2021)
This study entitled the effect of compensation on teacher teaching performance at SMPK 1 BPK Penabur Bandung using descriptive methods through a quantitative approach. The data model analysis used was literature study analysis and interviews. This study has 40 respondents. The results of the compensation calculation show that the WMS calculation has an average total indicator score of 2.58 or sufficient. Meanwhile, the Teacher Teaching Performance based on the WMS calculation has an average total indicator score of 3.11 or high. Researchers suggest that stakeholders can increase compensation to improve Teacher Teaching Performance.